Site-Specific Sequence Exchange Between Homologous and Non-homologous Chromosomes - Yin, Qian; Li, Ruyu; Ow, David W. (Frontiers in Plant Science, 2022)
Transgene integration typically takes place in an easy-to-transform laboratory variety before the transformation event is introgressed through backcrosses to elite cultivars. As new traits are added to existing transgenic lines, site-specific integration can stack new transgenes into a previously created transgenic locus. In planta site-specific integration minimizes the number of segregating loci to assemble into a breeding line, but cannot break genetic linkage between the transgenic locus and nearby undesirable traits. In this study, we describe an additional feature of an in planta gene-stacking scheme, in which the Cre (control of recombination) recombinase not only deletes transgenic DNA no longer needed after transformation but also mediates recombination between homologous or non-homologous chromosomes. Although the target site must first be introgressed through conventional breeding, subsequent transgenes inserted into the same locus would be able to use Cre-mediated translocation to expedite a linkage drag-free introgression to field cultivars.